49 PERLAKUAN PENCATATAN PADA KONVERSI MUSYARAKAH GUNA MENANGGULANGI PEMBIAYAAN BERMASALAH - Prasetyo, Aji (IQTISHODUNA, 2017)
Abstract: This research is the result of qualitative research which aims to analyze the conversion of musyarakahcontract in reducing the risk of murabaha problem and accountancy treatment on akad conversion in murabahahfinancing problem in syariah bank. Qualitative method used in this study with the type of case study research.The research data was collected by interviewing the informant, one of the heads of the finance division. Theresults showed that first, one of the efforts to overcome murabaha problem is restructuring in the form ofconversion to musyarakah financing. Secondly, conversion to musyarakah financing means closing the bookall relating to murabahah’s previous financing. Then, the remaining obligations that he can not afford areconverted into musharaka financing. The financing made for business activities with the banks and customersequally provide capital. In this case, the capital of the bank is the nominal residual liability of the customer andthe capital of the customer is the object of financing.